German Politics and Intergovernmental Negotiations on the Eurozone Budget - Donnelly, Shawn (2021)
This article examines selected political party positions on a Eurozone budget and fiscal transfers between 2018 and 2021. It posits that German government positions on common European debt and fiscal policy have undergone a significant but fragile shift. It must contend with continued domestic hostility before it can be said to be a lasting realignment. A great deal with depend less on the Social Democratic Party that is largely responsible for bringing it about with the support of German Greens, and more on the willingness of the Christian Democratic Union, their Bavarian sister party the Christian Social Union and the German voting public to adopt a more interventionist fiscal policy as well, generating shared commitments to economic policy at home and in Europe. That has not happened yet.